An updated checklist of recent non-marine Ostracoda (Crustacea) from Venezuela - Scott-Frías, Joxmer; González, Ernesto; Pardo, María José; Torres, Rubén; Higuti, Janet; Cohuo, Sergio; López, Carlos (Zootaxa, 2023)
Information on the known species diversity of the non-marine ostracods in Venezuela is compiled from the available literature. The review resulted in 34 species and two varieties, belonging to the superfamilies Cypridoidea and Cytheroidea. Of these, the presence of one species should be confirmed for the country. Furthermore, eight taxonomic entities classified with open nomenclature are mentioned. As additional contributions to the annotated list, georeferences of the records are included, as well as amendments in names and information for some localities. Finally, information about the distribution of some species, which were erroneously assigned to other biogeographic areas, is clarified, which is essential to optimizing the accuracy of subsequent analyses.